Improving MSME Performance Through Entrepreneurial Spirit and Business Motivation - Yudi Wahyudin Suwandi; Erwin Yulianto; Imas Komariah (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
A company must have business motivation and a strong entrepreneurial spirit. The aim of this research is to determine respondents' responses regarding the entrepreneurial spirit and motivation of the food processing MSME business in the city of Bandung. The method used in this research is a descriptive and verification method with a quantitative approach. Based on the results of statistical calculations, the magnitude of the path coefficient shows that entrepreneurial spirit has the greatest influence on MSME performance compared to business motivation, which shows that aspects such as self-confidence, courage to take risks, and innovation related to entrepreneurial spirit are more influential in improving performance. MSMEs are more than just business motivation. The dimension of self-confidence emerged as the most dominant aspect of entrepreneurial spirit, while originality (creativity and innovation) was ranked lowest. To improve entrepreneurial performance, individuals should focus on strengthening their originality by cultivating creativity and innovation, while continuously increasing their self-confidence. Business motivation has a positive and significant effect on the performance of MSMEs.